Analisis Kebutuhan Pengguna dan Sistem dalam Pengembangan Website Company Profile Biro Perjalanan Wisata Berbasis Web - Muhammad Encep; Syarif Hidayatulloh; Susi Maulidiah (LKP Unity Academy, 2026)
The development of information technology has driven digital transformation in various sectors, including tourism, which requires fast, accurate, and easily accessible information services. A company profile website serves as a strategic solution for delivering information and enhancing corporate image. However, system development without proper requirement analysis may result in systems that do not meet user needs. This study aims to analyze user and system requirements in developing a web-based company profile website for a travel agency. The method used is requirement engineering, consisting of requirement elicitation, requirement analysis, requirement specification, and requirement validation. Data were collected through observation, interviews, and questionnaires using a Likert scale. The results indicate that user requirements include access to tourism service information, booking features, and communication media with administrators. Meanwhile, system requirements consist of functional and non-functional aspects, emphasizing usability, performance, and interface design. The validation results show a high level of requirement suitability, indicating that the identified requirements can serve as a foundation for further system development.